Protective effect of pioglitazone on morphine-induced neuroinflammation in the rat lumbar spinal cord - Charkhpour, Mohammad (J Biomed Sci, 2015)
BACKGROUND: Morphine-induced tolerance is associated with the spinal neuroinflammation. The aim of this study was to explore the effects of oral administration of the pioglitazone, the peroxisome proliferator activated receptor gamma (PPAR-γ) agonist, on the morphine-induced neuroinflammation in the lumbar region of the male Wistar rat spinal cord. RESULTS: Co-administration of the pioglitazone with morphine not only attenuated morphine-induced tolerance, but also prevented the up-regulation of pro-inflammatory cytokines (tumor necrosis factor alpha, interleukin-1beta, and interleukin 6) and nuclear factor-kappa B activity. Administration of the GW-9662 antagonized the above mentioned effects of the pioglitazone. CONCLUSIONS: It is concluded that oral administration of the pioglitazone attenuates morphine-induced tolerance and the neuroinflammation in the lumbar region of the rat spinal cord. This action of the pioglitazone may be, at least in part, due to an interaction with the spinal pro-inflammatory cytokine expression and the nuclear factor-kappa B activity.